Dzieje bibliotek w ujęciu encyklopedycznym, na przykładzie polskich wydań encyklopedii przełomu XIX i XX wieku = The history of libraries from an encyclopedic perspective,exemplified by Polish editions of encyclopediasat the turn of the 20th century - Knyspel-Kopeć, Renata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The text discusses how libraries and their history were presented in Polish encyclopedic publications from the late 19th and early 20th centuries. Early encyclopedic works often defined a library simply as a collection of books, sometimes including manuscripts, engravings, and maps. Publications intended for children presented this information in short and accessible forms. Writers such as Feliks Bogucki and Stanisław Krzemiński introduced basic explanations of libraries in educational materials for young readers.A broader discussion of libraries appeared in works by Klementyna Hoffmanowa, who described famous libraries in Paris and Wrocław and encouraged young people to visit them to develop knowledge and humility. She also outlined the historical development of libraries, mentioning early collections in Jerusalem, the Library of Alexandria, private libraries in ancient Greece, and public collections in Rome, as well as medieval monastic libraries.Religious encyclopedias, such as the Ecclesiastical Encyclopedia edited by Michał Nowodworski, devoted extensive attention to church libraries and their role in preserving religious texts and manuscripts. These works emphasized the importance of cathedral and monastic libraries, which expanded through donations and became key centers of knowledge after the invention of printing.Overall, Polish encyclopedias of the period presented libraries not only as institutions preserving books but also as important cultural and educational symbols. They encouraged readers to use libraries, learn about world history and Polish heritage, and appreciate the cultural legacy preserved in books and manuscripts, especially during a time when Poland lacked political independence.
Keywords: biblioteki; historia; encyklopedie polskie; encyklopedie; biblioteki kościelne; biblioteki klasztorne; rękopisy; księgozbiory; dziedzictwo kulturowe; edukacja; tożsamość narodowa; Klementyna Hoffmanowa; Feliks Bogucki; Stanisław Krzemiński; Michał Nowodworski; Biblioteka Aleksandryjska; Biblioteka Watykańska; Biblioteka Załuskich; libraries; history; Polish encyclopedias; encyclopedias; church libraries; monastic libraries; manuscripts; book collections; cultural heritage; education; national identity; Library of Alexandria; Vatican library; Załuski library